A comparative study of small field total scatter factors and dose profiles using plastic scintillation detectors and other stereotactic dosimeters: The case of the CyberKnife. Issue 1 (4th January 2013) - Morin, Jonathan; Béliveau‐Nadeau, Dominic; Chung, Eunah; Seuntjens, Jan; Thériault, Dany; Archambault, Louis; Beddar, Sam; Beaulieu, Luc
Abstract : Purpose: : Small‐field dosimetry is challenging, and the main limitations of most dosimeters are insufficient spatial resolution, water nonequivalence, and energy dependence. The purpose of this study was to compare plastic scintillation detectors (PSDs) to several commercial stereotactic dosimeters by measuring total scatter factors and dose profiles on a CyberKnife system. Methods: : Two PSDs were developed, having sensitive volumes of 0.196 and 0.785 mm 3, and compared with other detectors. The spectral discrimination method was applied to subtract Čerenkov light from the signal. Both PSDs were compared to four commercial stereotactic dosimeters by measuring total scatter factors, namely, an IBA dosimetry stereotactic field diode (SFD), a PTW 60008 silicon diode, a PTW 60012 silicon diode, and a microLion. The measured total scatter factors were further compared with those of two independent Monte Carlo studies. For the dose profiles, two commercial detectors were used for the comparison, i.e., a PTW 60012 silicon diode and Gafchromics EBT2. Total scatter factors for a CyberKnife system were measured in circular fields with diameters from 5 to 60 mm. Dose profiles were measured for the 5‐ and 60‐mm cones. The measurements were performed in a water tank at a 1.5‐cm depth and an 80‐cm source‐axis distance. Results: : The total scatter factors measured using all the detectors agreed within 1% with the Monte Carlo values for cones of 20 mm or greater in diameter. For cones of 10–20 mm in diameter, the PTW 60008 silicon diode was the only dosimeter whose measurements did not agree within 1% with the Monte Carlo values. For smaller fields (<10 mm), each dosimeter type showed different behaviors. The silicon diodes over‐responded because of their water nonequivalence; the microLion and 1.0‐mm PSD under‐responded because of a volume‐averaging effect; and the 0.5‐mm PSD was the only detector within the uncertainties of the Monte Carlo simulations for all the cones. The PSDs, the PTW 60012 silicon diode, and the Gafchromics EBT2 agreed within 2% and 0.2 mm (gamma evaluation) for the measured dose profiles except in the tail of the 60‐mm cone. Conclusions: : Silicon diodes can be used to accurately measure small‐field dose profiles but not to measure total scatter factors, whereas PSDs can be used to accurately measure both. The authors' measurements show that the use of a 1.0‐mm PSD resulted in a negligible volume‐averaging effect (under‐response of ≈1%) down to a field size of 5 mm. Therefore, PSDs are strong candidates to become reference radiosurgery detectors for beam characterization and quality assurance measurements.